PENERAPAN METODE SIMPLEKS DALAM MENGOPTIMALISASI HASIL PENJUALAN PADA USAHA BERSKALA KECIL - Matheus Supriyanto Rumetna; Tirsa Ninia Lina; Jalminj Tindage; Frenny Silvia Pormes; Wiesje Ferdinandus (LPPM Universitas Widya Dharma, 2023)
Es Teler and Es Pisang Ijo are Indonesian food products in the form of ice snacks which are widely consumed by the public. These snacks are usually sold on the roadside. Mr. Leman, is one of the small-scale business actors who sell Es Teler and Es Pisang Ijo in Sorong City, Southwest Papua, to make ends meet. The problem faced by Mr. Leman in selling Es products is how to determine the optimal amount of Es Teler and Es Pisang Ijo sales production, so that maximum sales profits are obtained. This problem can be solved using the Simplex Method which is a part of Linear Programming (PL) and utilizing Information Technology, namely the POM-QM for Windows software to make the calculation process efficient. The method used in data collection is by interview and observation. The results of the analysis show that manual calculations using the simplex method and PL applications using the POM-QM for Windows software in optimizing sales obtain the same maximum profit, IDR 566,667 per day's production.